THE MICROCREDIT AS A SHORT-TERMS INSTRUMENT FOR SUSTAINABLE DEVELOPMENT THE NORTH-WEST REGION OF ALBANIA: SHKODRA CASE - Mimoza Zeneli; Armalda Reci (Agora International Journal of Economical Sciences (AIJES), 2023)
The Sustainable Development Goals are a global call to action to end poverty, protect the Earth's environment and climate, and ensure that people, regardless of location, can enjoy peace and well-being. Recently notice that Albanians tend to move abroad. Recent trend show that Albanians tend to move abroad. This is characteristic especially for the North of Albania. Shkodra region is a northwest part of Albania that is known for its wealth of natural recourses, culture and traditions. It is surrounded by a lake, a sea, and a river; also the people of Shkoder are called "The creedal of arts and knowledge". But the poverty indicators prove the opposite. The poverty in this region is nearly 15 %, and the unemployment level is very high. People tend to leave Shkodra. They have land and professions but they don't have the property legality and cash to exploit these natural resources. To have a sustainable development region, the government needs to take measures to help people to work their lands and to create their company. Interviewing a sample of 200 people in rural areas in Shkodra (borrowers/not borrowers) we notice that microcredit has a short-term impact in increasing their incomes and consequently contributes to reduction of immigration. Before and after is the method used for impact analysis in order to reach the above conclusion.
Keywords: 330